The economic effects and distributional implications of economic reform policies on the Indonesian economy: a CGE approach - Sugiyarto, Guntur (2000)
Having discussed issues of economic reform and its applications on the Indonesian economy followed by Indonesian SAMs and CGE applications, three CGE models representative to the economy were developed by using SAMs of 1985, 1990 and 1993 for analysing the effects of economic reform. Production is specified as a two-level nesting of CES functions and total production is allocated to domestic demand and exports. Producers are assumed to be indifferent between selling domestically and exporting, while for imports the `small country' assumption is adopted. Total demands are derived from composite commodities of domestically produced and imported commodities. Fixed and planned consumption patterns are assumed for households and government, which makes government saving a residual. Aggregate investment is accordingly fixed, reflecting the 'investment driven' nature of the economy.